2013
DOI: 10.1038/onc.2013.291
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implications of activation of the host gene (Dleu2) promoter for miR-15a/16-1 in chronic lymphocytic leukemia

Abstract: Genetic lesions and other regulatory events lead to silencing of the 13q14 locus in a majority of chronic lymphocytic leukemia (CLL) patients. This locus encodes a pair of critical pro-apoptotic microRNAs, miR-15a/16-1. Decreased levels of miR-15a/16-1 are critical for the increased survival exhibited by CLL cells. Similarly, in a de novo murine model of CLL, the NZB strain, germline-encoded regulation of the syntenic region resulted in decreased miR-15a/16-1. In this paper we have identified additional molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 66 publications
0
26
1
1
Order By: Relevance
“…For example, Morenos et al demonstrated that the DLEU2 locus and embedded miRNA cluster miR-15a/16-1 were commonly deleted in adult cancers and were shown to induce leukemogenesis (28). Kasar et al revealed that the DLEU2 promoter may augment chronic lymphocytic leukemia therapy by decreasing miR-15a/16-1 expression (29). These studies investigated the role of DLEU2 lncRNA or the DLEU2 protein as tumor suppressors, and our study first explored the molecular mechanism of circRNA-DLEU2 in AML.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Morenos et al demonstrated that the DLEU2 locus and embedded miRNA cluster miR-15a/16-1 were commonly deleted in adult cancers and were shown to induce leukemogenesis (28). Kasar et al revealed that the DLEU2 promoter may augment chronic lymphocytic leukemia therapy by decreasing miR-15a/16-1 expression (29). These studies investigated the role of DLEU2 lncRNA or the DLEU2 protein as tumor suppressors, and our study first explored the molecular mechanism of circRNA-DLEU2 in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Although MeCP2 binds to upstream genomic regions of both miR‐15a and its host Dleu2 , a noncoding RNA with tumor suppressor potential, MeCP2 seems to only regulate the expression of miR‐15a, not Dleu2, in developing neurons. While our finding seems to contradict what has been found in human leukemia cells, where these two genes are coexpressed (human 13q14) and coregulated , we did not assess whether these two genes can be corepressed or activated by other genes or stimuli. It is also possible that the regulation of miRNAs and their hosts is cell type‐dependent.…”
Section: Discussioncontrasting
confidence: 99%
“…The biogenesis of miRNAs starts with transcription of primary miRNAs (pri‐miRNAs) from the genome . The primary miR‐15a (pri‐miRNA) is expressed from a single‐copy genomic sequence located on mouse chromosome 14, which is 20 kb away from the nearest protein‐coding gene, Kcnrg , but within the intron of a noncoding RNA gene, Dleu2 . The genomic region immediately surrounding miR‐15a has a number of CpG dinucleotides with a nearby “AT‐hook” sequence motif (A/T ≥4) that can facilitate MeCP2 binding .…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the 54 lncRNAs are listed in Table 2 , and include oncogenic and tumor suppressor lncRNAs. HOTTIP is upregulated in hepatocellular carcinoma, osteosarcoma, lung, prostate and other cancers [ 30 ]; DLEU2 is deleted in lymphocytic leukemia and epigenetically silenced in myeloid leukemia [ 31 , 32 ]. Knockdown of HOTARM1 has been shown to promote proliferation in promyelocytic leukemia cells [ 33 ].…”
Section: Resultsmentioning
confidence: 99%